Extracellular microvesicles from astrocytes contain functional glutamate transporters: regulation by protein kinase C and cell activation - Gosselin, Romain-Daniel; Meylan, Patrick; Decosterd, Isabelle (Frontiers in Cellular Neuroscience, 2013)
Glutamate transport through astrocytic excitatory amino-acid transporters (EAAT)-1 and EAAT-2 is paramount for neural homeostasis. EAAT-1 has been reported in secreted extracellular microvesicles (eMV, such as exosomes) and because the protein kinase C (PKC) family controls the sub-cellular distribution of EAATs, we have explored whether PKCs drive EAATs into eMV. Using rat primary astrocytes, confocal immunofluorescence and ultracentrifugation on sucrose gradient we here report that PKC activation by phorbol myristate acetate (PMA) reorganizes EAAT-1 distribution and reduces functional [3H]-aspartate reuptake. Western-blots show that EAAT-1 is present in eMV from astrocyte conditioned medium, together with NaK ATPase and glutamine synthetase all being further increased after PMA treatment. However, nanoparticle tracking analysis reveals that PKC activation did not change particle concentration. Functional analysis indicates that eMV have the capacity to reuptake [3H]-aspartate. In vivo, we demonstrate that spinal astrocytic reaction induced by peripheral nerve lesion (spared nerve injury, SNI) is associated with a phosphorylation of PKC δ together with a shift of EAAT distribution ipsilaterally. Ex vivo, spinal explants from SNI rats release eMV with an increased content of NaK ATPase, EAAT-1 and EAAT-2. These data indicate PKC and cell activation as important regulators of EAAT-1 incorporation in eMV, and raise the possibility that microvesicular EAAT-1 may exert extracellular functions. Beyond a putative role in neuropathic pain, this phenomenon may be important for understanding neural homeostasis and a wide range of neurological diseases associated with astrocytic reaction as well as non-neurological diseases linked to eMV release.